DETERMINAN AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH PADA ORGANISASI PERANGKAT DAERAH PEMERINTAH PROVINSI PAPUA - Asrida Asrida; Meinarni Asnawi; Syaikhul Falah (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2018)
The purpose of this research is to examine and analyze the impact of the human resources quality, utilization of information technology, external pressure and presentation of financial report over the accountability of regional financial management the Papua province government. Sample taken from 47 regional working unit organisation (OPD), 2 person from each, total 94 respondents. Sampling method used is purposive sampling. The data collection was done with the direct survey while hypotheses tested empirically use path analisys. The results of this study explained that human resources quality, utilization of information technology, and external pressure directly influence to presentation of OPD’s financial report. Keywords: human resources quality, the use of information technology, external pressure, the presentation of the financial report, accountability